1992
DOI: 10.1016/0735-1097(92)90200-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of transpulmonary contrast-enhanced Doppler technique in the assessment of severity of aortic stenosis

Abstract: The transpulmonary contrast-enhanced Doppler technique using sonicated albumin is useful for assessing the severity of aortic stenosis even in patients with poor Doppler recordings, although the duration of signal enhancement might be affected by left ventricular systolic pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 22 publications
0
24
0
1
Order By: Relevance
“…Underestimation is a valid concern when confronted with decision for surgery. Contrast has been shown to result in an improvement in the determination of the peak Doppler velocity AS profile, allowing a more accurate trans-aortic gradient estimation (Nakatani S et al, 1992). Importantly, in this study, the authors noted that patients with weak Doppler signals demonstrated improvements in their image profiles, but even those with adequate unenhanced Doppler signals were further improved by the use of contrast.…”
Section: Left Heartmentioning
confidence: 50%
“…Underestimation is a valid concern when confronted with decision for surgery. Contrast has been shown to result in an improvement in the determination of the peak Doppler velocity AS profile, allowing a more accurate trans-aortic gradient estimation (Nakatani S et al, 1992). Importantly, in this study, the authors noted that patients with weak Doppler signals demonstrated improvements in their image profiles, but even those with adequate unenhanced Doppler signals were further improved by the use of contrast.…”
Section: Left Heartmentioning
confidence: 50%
“…Intravenous sonicated albumin has also been utilized to improve left-sided Doppler signals across the aortic valve [19]. Since the albumin microbubbles are smaller, the major limitation with this application has been the short duration of signal enhancement in the patients with aortic stenosis due to pressure instability of albumin microbubbles.…”
Section: Clinical Implications Of a Larger Microbubblementioning
confidence: 98%
“…Some patients with aortic stenosis may have suboptimal acoustic window or Doppler recordings, and contrast echocardiography may be of help in these cases [18,19]. In one study by Nakatani et al [20], the transaortic Doppler recording was of sufficient quality after intravenous injection of sonicated albumin in patients in which the aortic velocity envelope was too indistinct to determine the peak velocity before contrast administration. In that study, aortic valve area measured after contrast administration had a strong correlation with that obtained invasively by Gorlin's formula [20].…”
Section: Contrast Echocardiographymentioning
confidence: 99%